The Father of Football Fiction? A.S. Hardy and the popularisation of Association Football fiction in the boys' story papers of the Amalgamated Press, c1900–1939. Issue 1 (2nd January 2022) - Jackson, Alexander
ABSTRACT: Under the pen-name of A.S. Hardy, Arthur Joseph Steffens was one of the leading writers of boys' football stories in the first decades of the twentieth century. Building upon the work of John Springhall, Kelly Boyd, Ernest Turner, Dave Russell and Ali Melling, this article seeks to broaden our knowledge of how football fiction first developed. It does this by exploring the life and stories of A.S. Hardy, as well as some of his contemporaries at the Amalgamated Press. The principal sources are original boys' papers held at the British Library and census records. The article explores three key areas. Firstly, an overview is provided of Hardy's life and career, placing his work within the wider growth of boys' story papers and the success of the Amalgamated Press in the late nineteenth and early twentieth century. Secondly, it explores how Hardy successfully pioneered the writing of stories placed within the contemporary world of professional football. Finally, it addresses how established conventions of masculine and heroic behaviour were adapted and explored within football stories. It will be argued that Hardy played an important part in developing and popularising the fictional football story in its modern format.